Nitroxide mediated copolymerization of acrylates, methacrylates and styrene: The importance of side reactions in the polymerization of acrylates. (January 2019) - Simula, Alexandre; Ballard, Nicholas; Aguirre, Miren; Leiza, Jose R.; Es, Steven van; Asua, José M.
Graphical abstract: Highlights: The presented alkoxyamine can produce block/random copolymers with n-butyl acrylate (BA). Macro-alkoxyamines can be prepared depending on temperature, solids content and with a co-monomer. The influence of backbiting and β -scission can be modeled and diminished with optimal conditions. Abstract: The ability to (co)polymerize acrylates, methacrylates and styrene with one alkoxyamine/nitroxide has been regarded as challenging in nitroxide mediated polymerization (NMP). The alkoxyamine 3-(((2-cyanopropan-2-yl)oxy)(cyclohexyl)amino)-2, 2-dimethyl-3-phenylpropanenitrile (Dispolreg 007) has recently emerged as a robust regulator to mediate the (co)polymerization of methacrylates and styrene. Herein, the versatility of the alkoxyamine is tested to produce random and block copolymers based on n -butyl acrylate (BA). The formation and influence of dead polymer (mostly macromonomers) was studied for the homopolymerziation of n -butyl acrylate. At temperatures above 100 °C, control over the polymerization could be retained up to about 50% conversion, with relatively narrow molar mass distributions ( M n = 34000 g·mol −1, Ð ∼ 1.7). Above this conversion side reactions, namely β -scission of mid-chain radicals generated by chain transfer to polymer and monomer self-initiation led to loss of control. This effect could be mitigated by lowering to 50 wt% the concentration of BA and/or by lowering the temperature, or by copolymerizing BA with MMA or styrene. The chain extension of acrylate based macro-alkoxyamines led to non linear structures, due to the presence of macromonomers and residual dead chains during the production of PBA macro-alkoxyamines.